(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the pivotal role of Dr. B.R. Ambedkar in awakening and mobilizing lower caste consciousness in India. Through an analysis of his writings, speeches, and political actions, we explore how Ambedkar’s efforts led to a significant shift in the socio-political landscape of India, particularly for the Dalits and other marginalized communities. The research highlights Ambedkar’s multifaceted approach, encompassing legal reforms, social movements, and educational initiatives, in challenging the caste system and promoting equality and dignity for all.